This is not a remix : piracy, authenticity and popular music - Borschke, Margie (New York, NY : Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2017)
"Widespread distribution of recorded music via digital networks affects more than just business models and marketing strategies; it also alters the way we understand recordings, scenes and histories of popular music culture. This Is Not a Remix uncovers the analog roots of digital practices and brings the long history of copies and piracy into contact with contemporary controversies about the reproduction, use and circulation of recordings on the internet. Borschke examines the innovations that have sprung from the use of recording formats in grassroots music scenes, from the vinyl, tape and acetate that early disco DJs used to create remixes to the mp3 blogs and vinyl revivalists of the 21st century. This is Not A Remix challenges claims that 'remix culture' is a substantially new set of innovations and highlights the continuities and contradictions of the Internet era. Through an historical focus on copy as a property and practice, This Is Not a Remix focuses on questions about the materiality of media, its use and the aesthetic dimensions of reproduction and circulation in digital networks. Through a close look at sometimes illicit forms of composition-including remixes, edits, mashup, bootlegs and playlists-Borschke ponders how and why ideals of authenticity persist in networked cultures where copies and copying are ubiquitous and seemingly at odds with romantic constructions of authorship. By teasing out unspoken assumptions about media and culture, this book offers fresh perspectives on the cultural politics of intellectual property in the digital era and poses questions about the promises, possibilities and challenges of network visibility and mobility."--Publisher's description.
1. This is not a remix -- 1.1. Introduction -- 1.2. Critical approach -- 2. Copy, a brief history -- 2.1. The ghost in the digital machine -- 2.2. The trouble with media history -- 2.3. "Again, back": Repetition and music's materiality -- 3. The rhetoric of remix -- 3.1. Remix as trope -- 3.2. The extended remix: In the press -- 3.3. The extended remix: Scholarly use -- 3.4. Lawrence Lessig's "Remix Culture" -- 3.5. Remix as resistance -- 3.6. Why the history of remix matters -- 4. Disco edits: Analog antecedents and network bias -- 4.1. What a difference a record makes -- 4.2. Interrupting the rhetoric of remix -- 4.3. Disco edits, a technical distinction -- 4.4. Hang the DJ -- 4.5. Walter Gibbons, the break, and the edits that made disco -- 4.6. Let your body talk -- 4.7. Are samples copies? -- 4.8. Parasites, pirates, and permission -- 4.9. Digital revival and an analog persistence -- 4.10. Credit to the edit -- 5. The new romantics -- 5.1. Piracy's long history -- 5.2. MP3 blogs as social media -- 5.3. Material media: MP3 blogs as artifacts and practices -- 5.4. Provenance as metadata -- 5.5. Rethinking participation and the folk aesthetic -- 5.6. Countercultures and anticommercialism -- 5.7. Networking authenticity -- 5.8. Analog antecedents: Harry Smith's mystical collection -- 5.9. Copies, networks, and a poetics of encounter -- 6. Copies and the aesthetics of circulation.
Includes bibliographical references and index.
Keywords: Remixes -- History and criticism; Sound recordings -- Social aspects; Popular music -- Social aspects; Music and the Internet